Physical chemical characterization, bioactive compounds and antioxidant activity of Pachira aquatica Aublet almonds (Research, Society and Development, 2020)
The Pachira aquatica Aublet, belonging to the Malvaceae family, is a tree of variable size, annually produces large quantities of capsule type fruits, in which its seeds remain stored. Even though it is commonly found in southern Mexico and Brazil, there are few studies on its composition. Therefore, the objective of this study is to demonstrate the characteristics of this fruit by means of physical analyzes and to evaluate the bioactive compounds of the almonds in the raw, cooked and roasted forms. Type of research laboratory and quantitative. The almonds showed high content of lipids (above 30%), proteins (above 15%), pH (above 5.66), total soluble solids (above 15º Brix) and total titratable acidity (above 3%). The roasted almond had a higher content of phenolic compounds, flavonoids and carotenoids. In the raw form, a higher content of antioxidant activity, anthocyanins and condensed tannins was obtained. The cooked almond presented intermediate values in all data on bioactive compounds and antioxidant activity.